Flickr hacks - Bausch, Paul (O'Reilly, 2006)
"Over two million registered Flickr users and counting have discovered the ease and fun of organizing their photo libraries, showing off their favorite pictures to the world, and securely sharing their private pictures with friends, family, or ad hoc groups. But Flickr's own plethora of intuitive menus, options, and features just scratches the surface. Flickr Hacks goes beyond the basics of storing, sorting, and sharing your photos to the much bigger playground of what's possible. Whether you're a beginner looking to manage your metadata and play with tags, or a programmer in need of a detailed reference of Flickr API methods, you'll find what you're looking for here."--Provided by publisher.